NSTX-U Personnel Safety System: Safety Instrumented System Development and Design. (17th November 2021) - Petrella, Joseph R.; Stevenson, Timothy; Cropper, Mark; Sichta, Paul; D'Agostino, Michael; Thomas, Moheb; Zhao, Xin; Hines, Clarence
Abstract: A safety instrumented system design guided by the International Electrotechnical Commission (IEC) standard IEC/ISA 61511 has been developed to ensure personnel protection from direct radiation and magnetic field hazards identified for the National Spherical Torus eXperiment–Upgrade (NSTX-U) fusion experiment at the Princeton Plasma Physics Laboratory. A layer of protection analysis was performed to develop the performance requirements of the system. A design was developed that incorporated three independent protection layers including configuration-managed safeguards (for electrical hazards), a trapped key system, and a dual chain redundant safety instrumented system. Extensive value engineering was undertaken to supplement existing infrastructure to be compliant with current industry standards and best engineering practices. The development and design of the safety instrumented system is presented.